The Transformation of Generation Z’s Religiosity in the Context of Modernity: The Role of Formal Spirituality and Spiritual Well-Being - Muhammad Luthfiannoor Habibi; Akmal Safi`i; Muhammad Afdhal Ridho; Surawan Surawan (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
With modernity and digital acceleration shaping how young people see religion, being religious isn't just about following rituals anymore but also about having a reflective and personal spiritual experience. You can see this with Gen Z, who still practice formal spirituality while also building spiritual well-being through contemplative experiences and searching for meaning in their context. Research aims to analyze how Generation Z's religious transformation takes place in the context of modernity and how formal spirituality contributes to the formation of spiritual well-being. This research finds that the transformation of Generation Z's religiosity does not lead to a weakening of formal religion, but rather to a shift in orientation toward a more internal and existential meaning. Formal spirituality continues to function as the foundation of religiosity, enriched by reflective and personal experiences in building spiritual well-being. Formal spirituality still holds an important role in shaping the spiritual well-being of Generation Z amid modernity and digital culture. Formal religious practices are not only understood as ritual obligations but also as a source of meaning in life and a coping mechanism in facing the pressures of modern life. These findings confirm that formal spirituality remains relevant as the foundation of spiritual well-being for the younger generation in the modern era.